Toxicity of Miana Leaf (Coleus blumei) Extract Against Houseflies (Musca domestica) - Surahmaida, Surahmaida; Umarudin, Umarudin (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Houseflies (Musca domestica) is an disease-carrying insect that plays an important role in the spread of disease in humans and animals. One way to control houseflies is using Miana leaves (Coleus blumei) as botanical pesticide. The purpose of this study was to determine the chemical compounds contained in Miana leaf as well as determine the optimal concentration of Miana leaf extract in causing knockdown effect in houseflies. Miana leaf fine powder was soaked with methanol (maceration) for 3 days followed byphytochemical screening (chemical reagents and Gas Chromatography Mass Spectrophotometry (GCMS) and anti-houseflies toxicity tests. Testing of methanolic extract of Miana leaves was made in the form of spray using the knockdown method at concentrations of 5%, 10%, 20%, 30% and 40% and observed in 5, 10 and 15 minutes. The results of phytochemical screening with chemical reagents showed that the extract contained alkaloids, tannins, flavonoids, saponins and terpenoids; while the results of GCMS analysis showed 8 bioactive compounds. The results of the study revealed that at a concentration of 30% and 40%, methanolic extract of Miana leaves could result in a knockdown effect that was accompanied by death with a percentage value of 100% in the first 5 minutes of observation. This research shows that methanolic extract of Miana leaves can be used as an alternative to botanical pesticides in controlling houseflies (Musca domestica).